Structure-function analysis of vascular tethering molecules using atomic force microscope - Wu, Tao (Georgia Institute of Technology, 2010)
During hemostatic and inflammatory responses, cell adhesion molecules play a major role in regulating the leukocytes and platelets adhesion to vascular surfaces under the hydrodynamic environment of the circulation. Selectin-ligand interactions (bonds) mediate leukocyte rolling on vascular surfaces. The molecular basis for differential ligand recognition by selectins is poorly understood. Using atomic force microscopy (AFM), the kinetics of three mutants L-selectin interacting with surrogates of PSGL-1 and PNAd, is compared with those of wild-type L-selectin. The interaction between glycoprotein Ib (GPIb) and von Willebrand Factor (VWF) mediates platelet translocation at the vascular vessel damage sites, which plays a critical role in initiating the platelets adhesion and thrombus formation. Translocation of platelets on VWF requires a shear threshold, suggesting a possible catch bond at work there. We characterized the kinetics of GPIbα interacting with VWF A1 domain, confirming the catch bond existed. Two type 2B VWD A1 mutants eliminated the catch bond and gave longer low force lifetimes. The prolonged lifetimes at low force resulted in more agglutination of platelets with A1 coated microspheres in flow. During the process of hemostasis, the size of prothrombotic ULVWF affects the affinity of VWF to platelets bearing GPIbα on the membrane. ADAMTS13 has been identified and characterized as a multi-domain metalloprotease that regulate the size of ULVWF. We studied how force regulated the binding and cleavage of ADAMTS13 on VWF. We found the cleavage effects could only be observed after the catastrophic structural change of A1A2A3. The unfolding exposed the ADAMTS13 cleavage site and favored the cleavage. Two protocols using different stretching molecules (GPIbα and CR1) and A1A2A3 immobilization methods revealed the cleavage effects diminished with increasing stretching force. This study elucidated mechanisms of the binding kinetics of L-selectin with different structure components from PSGL-1 and PNAd by structural variants. It also provided new insights into our current knowledge of the dynamic adhesion and regulation of GPIbα-VWF interaction in vivo. Using single molecule method, the chemical catalytic reaction between enzyme and substrate has been targeted. These results help us understand this important enzyme-substrate interaction involved in the hemostasis.